2020
DOI: 10.1021/acscatal.0c03652
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hydrophilic Conjugated Microporous Polymers for Efficient Visible Light-Driven Nicotinamide Adenine Dinucleotide Regeneration and Photobiocatalytic Formaldehyde Reduction

Abstract: Recently, photobiocatalysis with oxidoreductases, inspired by natural photosynthesis, has drawn increasing attention due to its high catalytic efficiency and selectivity. However, although an important cofactor for the activation of redox enzymes, nicotinamide adenine dinucleotide (NADH) suffers from the drawbacks of cost and limited stability. Moreover, the design of an effective NADH regeneration system remains a huge challenge. Here, we report a visible light-driven conjugated microporous polymer DBTS-CMP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 64 publications
2
44
0
Order By: Relevance
“…Results showed that the methanol concentration was maintained after six rounds of experiments, indicating that the enzyme activity was maintained and that the enzyme leakage was negligible. For most published enzyme-immobilized systems, ,, the process typically involved chemical reaction and an unfavorable solvent, which is harmful for enzyme activity and stability. All in all, such a photosynthesis system showed outstanding performance on methanol production with a facile synthesis, which was a promising way to produce methanol driven by unlimited solar energy.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the methanol concentration was maintained after six rounds of experiments, indicating that the enzyme activity was maintained and that the enzyme leakage was negligible. For most published enzyme-immobilized systems, ,, the process typically involved chemical reaction and an unfavorable solvent, which is harmful for enzyme activity and stability. All in all, such a photosynthesis system showed outstanding performance on methanol production with a facile synthesis, which was a promising way to produce methanol driven by unlimited solar energy.…”
Section: Resultsmentioning
confidence: 99%
“…After that, various types of organic polymers for photocatalytic hydrogen evolution have been widely studied, such as conjugated microporous polymers (CMPs), linear conjugated polymers and covalent organic framework materials, etc. 12–14 Among them, CMPs is emerging class of organic porous materials with large π-conjugated framework and many nanoscale pores. 15–17 More importantly, the energy band structure, optical absorption and pore size of CMPs can be fine-tuned by changing the chemical structure.…”
Section: Introductionmentioning
confidence: 99%
“…Sunlight provides sustainable energy to drive challenging chemical reactions with semiconductor materials through an environmentally friendly route. [14][15][16][17][18][19] Substantial research efforts have mainly focused on promoting exciton dissociation of the semiconductors by means of textural tailoring, optical property optimization, and surface kinetic control. [20][21][22] Recently, attention has been paid to hybrid photocatalysis, which accelerates charge separation by establishing electron transport chains between semiconductor and molecular catalyst, provides a feasible and efficient photocatalytic platform for continuous electron output to substrate, and is fully accessible to the toolbox of valuable organic synthesis.…”
Section: Introductionmentioning
confidence: 99%